Government innovation policy and higher education: the case of Shenzhen, China. Issue 2 (3rd March 2020) - Mok, Ka-Ho; Welch, Anthony; Kang, Yuyang
ABSTRACT: Set against broader theoretical debates regarding the role of the developmental state in driving social and economic developments in Asia, particularly in higher education and research, the present article critically examines the synergies between government, enterprise and universities in China, in promoting innovation-centric entrepreneurship. The example of Shenzhen, China, including its response to the Greater Bay Area initiative, highlights how new governance modalities have emerged to embrace multiple actors and diverse non-state/non-government sectors in support of innovation-centric entrepreneurial ventures. Our analysis reveals new forms of network governance. These include hybrid organisations that have become more proactively engaged in fostering a spirit of entrepreneurship, including in the higher education sector, albeit against a backdrop of tensions in the mainland governance model, between the drive for innovation and re-assertion of Party control.